THE EVOLUTION OF THE ACCELERATION MECHANISMS OF COSMIC RAYS AND RELATIVISTIC ELECTRONS IN RADIO GALAXIES - Tsvyk, N. (Одеські астрономічні публікації, 2013)
There are estimated an efficacy for different acceleration mechanisms of e- and p-cosmic rays (CRs) in radio galaxies, using an evolution model for jet gaps and shock fronts with a turbulence. It is shown that diffusion shock acceleration of the CRs is the most efficient mechanism in the FR II radio galaxies (RGs). At the same time, there are a break-pinch mechanism (for a short-term at a jet gap moment), and a stochastic turbulent mechanism (for an all time when RG exist), that to play a grate part in acceleration of the CRs (give to 10-50 % of the all acceleration efficiency). It is predicted what properties of radio emission spectra give us to recognize a type of acceleration mechanisms of e-CR in the RG.